Tolerogenic Nanoparticles Induce Antigen-Specific Regulatory T Cells and Provide Therapeutic Efficacy and Transferrable Tolerance against Experimental Autoimmune Encephalomyelitis - LaMothe, Robert A.; Kolte, Pallavi N.; Vo, Trinh; Ferrari, Joseph D.; Gelsinger, Tracy C.; Wong, Jodie; Chan, Victor T.; Ahmed, Sinthia; Srinivasan, Aditi; Deitemeyer, Patrick; Maldonado, Roberto A.; Kishimoto, Takashi K. (Frontiers in Immunology, 2018)
T cells reacting to self-components can promote tissue damage when escaping tolerogenic control mechanisms and may result in autoimmune disease. The current treatments for these disorders are not antigen-specific and can compromise host immunity. We have previously demonstrated that tolerogenic nanoparticles (tNPs) comprised of biodegradable polymers that encapsulate rapamycin co-administered with encapsulated or free antigen (Ag) are capable of inhibiting antigen-specific transgenic T cell proliferation and inducing antigen-specific regulatory T cells (Tregs). Here we further show that tNPs can trigger the expansion of endogenous Tregs specific to a target antigen. The proportion of antigen-specific Treg to total antigen-specific T cells remains constant even after subsequent antigen challenge in combination with a potent TLR7/8 agonist or complete Freunds adjuvant (CFA). Treatment with tNPs provide therapeutic protection in relapsing experimental autoimmune encephalomyelitis (rEAE) that can be transferred to naïve animals. Furthermore, mice treated with tNPs do not develop EAE after adoptive transfer of encephalitogenic T cells. These findings describe a potent therapy to expand Ag-specific Tregs in-vivo and suppress T cell-mediated autoimmunity.